First Person Jewish - Lebow, Alisa (Book collections on Project MUSE., 2008)
Alisa S. Lebow examines films from Jewish artists to reveal how the postmodern impulse to turn the lens inward intersects provocatively (and at times unwittingly) with historical tropes and stereotypes of the Jew. Using a multidisciplinary approach Lebow shows how this form of self-expression is challenging both autobiography and documentary and, in the process, changing the art of cinema and recording the cultural shifts of our time.